A scoping review on innovative methods for personality observation - Mosca, Lucia Luciana; Continisio, Grazia Isabella; De Lucia, Natascia; Gigante, Elena; Guerriera, Carmela; Maldonato, Nelson Mauro; Moretto, Enrico; Ragozzino, Ottavio; Rosa, Veronica; Scognamiglio, Chiara; Stanzione, Roberta; Cantone, Daniela (Frontiers in Psychology, 2023)
Background. Personality's investigation has characterized as a central area of research for psychology Identifying and observing the people's typical ways of "being in the world" has made possible to define the predictability of a pattern of behavioral responses. There is a strand of research that makes : description of personality through methodologies and indicators not usually used by psychology, bu scientifically validated through standardized procedures. Such studies reflect the emerging need to have to consider the human being in its complexity. Objective. In this review, attention is focused on highlighting publications in the literature that have included the use of unconventional methods in the study of nonpathological personality, based on the Big Five theoretical reference model. Design. Online databases were used to identify papers published 2011-2022, from which we selected 16 publications from different resources, selected according to criteria established in advance and describe in the text. Results. The selected studies were grouped according to the particular method of investigation o description of personality used. Four broad thematic categories were identified: bodily and behavioral element; semantic analysis of the self-descriptions provided; integrated-type theoretical background; and use of machine learning methods. Conclusions. This review has the main purpose to highlight how the use of observational models base on aspects previously considered as scientifically uninformative (body, linguistic expression environment) proves to be a valuable resource for drawing.